2002
DOI: 10.1034/j.1398-9995.2002.23688.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary leukotriene levels are increased during exacerbation of atopic eczema/dermatitis syndrome. Relation to clinical status

Abstract: Our results point to enhanced biosynthesis of Cys-LTs during the AEDS exacerbations. Inflammatory cells, e.g. eosinophils are the most probable source of Cys-LTs. A strong correlation between Cys-LT levels and clinical status may in part explain preliminary clinical observations of efficacy of leukotriene antagonists in alleviating symptoms of AEDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
2
11
0
1
Order By: Relevance
“…Although the role of cysteinyl LTs in the inflammation of AD is unclear, several reports in the literature, but not all (Veien et al, 2005), detail improvements in patients (adult and children) with moderate to severe AD with the use of LTRAs at the doses generally recommended for asthma treatment Leonardi et al, 2007;Broshtilova and Gantcheva, 2010). In support, there is also the evidence that elevated levels of LTE 4 have been found in the urine of patients with AD (Adamek-Guzik et al, 2002;Øymar and Aksnes, 2005). Chronic urticaria (CU) may manifest as an idiopathic reaction or as a reaction to a known cause, such as cold, pressure, food additives, or NSAIDs; however, this does not occur with selective COX-2 inhibitors (Zembowicz et al, 2003).…”
Section: New Potential Therapeutic Applications Of Leukotriene Recsupporting
confidence: 55%
“…Although the role of cysteinyl LTs in the inflammation of AD is unclear, several reports in the literature, but not all (Veien et al, 2005), detail improvements in patients (adult and children) with moderate to severe AD with the use of LTRAs at the doses generally recommended for asthma treatment Leonardi et al, 2007;Broshtilova and Gantcheva, 2010). In support, there is also the evidence that elevated levels of LTE 4 have been found in the urine of patients with AD (Adamek-Guzik et al, 2002;Øymar and Aksnes, 2005). Chronic urticaria (CU) may manifest as an idiopathic reaction or as a reaction to a known cause, such as cold, pressure, food additives, or NSAIDs; however, this does not occur with selective COX-2 inhibitors (Zembowicz et al, 2003).…”
Section: New Potential Therapeutic Applications Of Leukotriene Recsupporting
confidence: 55%
“…Patients were studied at three time‐points: during the exacerbation (day 0) and after 4 and 12 weeks of the treatment with oral antihistamine (cetirizine; purchased from UCB Pharma, Bulle, Switzerland) and topical steroid (mometasone; purchased from Schering–Plough AG, Heist‐op‐den Berg, Belgium) applied on lesional skin. At these time‐points skin, nose and throat were examined for the colonization with S. aureus , immunological tests were carried out, and clinical status was assessed using severity scoring of atopic dermatitis (SCORAD) as used before [24]. Clinical status was also additionally assessed in all patients 12 weeks after conclusion of the treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The total IgE levels were determined in sera from AD patients by ELISA, using AlaSTAT total IgE test (DPC Biermann, Bad Neuheim, Germany) as described before [24]. Levels of total IgG, IgM and IgA were determined by nephelometry (Behring Nephelometer 100, Behring AG, Marburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…This increased urinary excretion appears to be correlated with the severity of skin lesions and eosinophil counts during exacerbation of the disease [49]. However, there are conflicting data since some authors have found that urine LTE 4 levels were not increased during or after the acute exacerbation of atopic dermatitis, compared with the normal range [50].…”
Section: Leukotrienes In Allergic Diseasesmentioning
confidence: 96%